Spatial and temporal distribution of methane emissions from a covered landfill equipped with a gas recollection system - Gonzalez-Valencia, Rodrigo; Magana-Rodriguez, Felipe; Martinez-Cruz, Karla; Fochesatto, Gilberto J.; Thalasso, Frederic (My University, 2021)
A previously developed surface probe method, which allows for instantaneous methane (CH4) flux measurement, was used to establish CH4 emission maps of a municipal landfill with a final clay cover and equipped with a gas recollection system. In addition to spatial variations, the method was applied at 7 different times over a total timeframe of 65 h and under similar weather conditions to determine the intrinsic temporal variations of CH4 emissions; i.e., the temporal variation related to the dynamic of the landfill rather than the one driven by external factors. Furthermore, continuous CH4 fluxes, with a data acquisition frequency of 1 Hz, were measured during 12 h at a single position, and for one hour at 22 locations of the landfill, spanning a large range of CH4 emission magnitudes. A simple model for the numerical characterization of spatiotemporal variability of the landfill emission was used and allowed us to separately quantify the temporal and spatial variability. This model showed that, in the landfill tested, the temporal distribution of CH4 emissions resulted more homogeneous than the spatial distribution. Other attributes of the temporal and spatial distributions of CH4 emissions were also established including the anisotropic nature of the spatial distribution and, contrastingly, the stochastic temporal variability of such emissions. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: homogeneity; variability; ch4; landfill cover